Aleitamento materno e seus desafios: a importância da assistência de enfermagem na prevenção ao desmame precoce - Silva, Patricia Corrêa (My University, 2021)
Objectives: Identify in the scientific literature the role of nursing care in the breastfeeding process and its actions in preventing early weaning. Methods: Systematic bibliographic literature review with qualitative integration, through consultation in the Virtual Health Library (BVS in Portuguese) database, using the descriptors Nursing Assistance; Breastfeeding and Nursing Assistance; Prevention of weaning. Were included Brazilian research, published in national and international journals, in Portuguese, English, or Spanish, in the period from 2018 to July/2021. Results: Sixteen articles were selected from 1,319 retrieved. Main contributions of nurses: Factors associated with breastfeeding in the first hour of life; Promotion of breastfeeding in prenatal care; Nursing actions in Pregnant Women's Care; The nursing team's perception of breastfeeding; Nurse's role in the clinical management of breastfeeding; Delivery and birth care; Discharge preparation for home care of low-risk newborns; Effect of an educational intervention for breastfeeding; Nurse's contribution to breastfeeding in primary care; Influence of health education on self-efficacy in breastfeeding; Analysis of practices in childbirth care and hospital postpartum; Consultancy on breastfeeding during the COVID-19 pandemic; Skin-to-skin contact and breastfeeding of newborns; Breastfeeding under the aegis of support networks; Nursing practices and the socio-cultural influence on adherence to breastfeeding; Breastfeeding self-efficacy among mothers of premature babies. Conclusion: The nursing professional has a fundamental role in reversing/improving the current unsatisfactory situation of breastfeeding. However, only technical knowledge on the subject is not enough, it is necessary to have a careful, comprehensive, and humanitarian look. Each mother is the protagonist of her breastfeeding process and, therefore, also responds differently. This clinical/professional look must necessarily seek to understand and value it in its historical, cultural, social, and human aspects. The nurse is a refuge, sustenance, and support, as well as a source of accurate information and humanized care. [resumo fornecido pelo autor]
Objetivos: Identificar na literatura científica o papel da assistência em enfermagem no processo do aleitamento materno e suas ações na prevenção ao desmame precoce. Métodos: Revisão de literatura do tipo bibliográfica sistemática com integração qualitativa, através de consulta na base de dados da biblioteca virtual de saúde (BVS), utilizando os descritores Assistência em Enfermagem; Aleitamento Materno e Assistência em Enfermagem; Prevenção ao desmame. Foram incluídas pesquisas brasileiras, publicadas em periódicos nacionais e internacionais, em português, inglês ou espanhol, no período de tempo de 2018 a julho/2021. Resultados: Dezesseis artigos selecionados de 1.319 recuperados. Principais contribuições dos enfermeiros: Fatores associados ao aleitamento materno na primeira hora de vida; Promoção do aleitamento materno no pré-natal; As ações de Enfermagem no Cuidado à Gestante; Percepção da equipe de enfermagem frente ao aleitamento materno; Atuação do enfermeiro no manejo clínico da amamentação; Atenção ao parto e nascimento; Preparo de alta para o cuidado domiciliar de recém-nascidos de baixo risco; Efeito de uma intervenção educativa para o aleitamento materno; Contribuição do enfermeiro ao aleitamento materno na atenção básica; Influência da educação em saúde na autoeficácia em amamentar; Análise de práticas na assistência ao parto e pós-parto hospitalar; Consultoria em amamentação durante a pandemia COVID-19; Contato pele a pele e aleitamento materno de recém-nascidos; A amamentação sob a égide de redes de apoio; Práticas de enfermeiros e a influência sociocultural na adesão ao aleitamento materno; Autoeficácia em amamentar entre mães de bebês prematuros. Conclusão: O profissional de enfermagem tem papel fundamental na reversão/melhoria do quadro insatisfatório atual de aleitamento materno. Não basta, entretanto, apenas conhecimento técnico sobre o assunto, é preciso um olhar atento, abrangente e humanitário. Cada mãe é protagonista do seu processo de amamentar e, portanto, também o responde de maneira diferente. Esse olhar clínico/profissional necessariamente deve buscar compreende-la e valorizá-la em seus aspectos histórico, cultural, social e humano. O enfermeiro é amparo e suporte, além de fonte de informação precisa, e de acolhimento humanizado. [resumo fornecido pelo autor]
Keywords: Enfermeiros; Enfermagem; Amamentação; Lactentes - Desmame